Non-parathyroid hypercalcemia in a patient with new-onset hyperthyroidism and silicone-induced granulomas: case report - Montefusco, Laura; Rossi, Giada; Petria, Iulia; Pastore, Ida; Fiorina, Paolo (Frontiers in Endocrinology, 2025)
BackgroundHypercalcemia is a frequent occurrence in hospitalized patients. It can vary in presentation and severity, and appropriate treatment requires targeting of the underlying condition. Rarer causes of hypercalcemia, such as hyperthyroidism and granulomatous diseases, need to be addressed after excluding the more prevalent etiologies, namely primary hyperparathyroidism and malignancies. We report a case of moderate hypercalcemia in a patient with HIV-positivity with new-onset autoimmune hyperthyroidism as well as concomitant chronic granulomas due to silicone injections.Case summaryA 61-year-old patient presented with generalized malaise, asthenia, dyspnea and dysphagia associated with rapid weight loss and recurrent panic attacks. Biochemical work-up revealed moderate hypercalcemia and overt hyperthyroidism with positive anti-TSH-receptor antibodies. Hydration, loop diuretics and methimazole were initiated immediately. Suppressed parathyroid hormone (PTH) levels excluded PTH-mediated hypercalcemia (e.g., primary hyperparathyroidism) and among causes of non-PTH-mediated hypercalcemia, malignancies were excluded. Granulomas secondary to past silicone injections were also found in our patient, however normal 1,25-dihydroxy vitamin D3 levels. Treatment of hyperthyroidism with normalization of thyroid function tests was simultaneously followed by improvement of calcium and PTH levels supporting the diagnosis of hypercalcemia secondary to Graves’ disease.Learning pointsHyperthyroidism is a rare cause of hypercalcemia, but it has to be considered in suggestive clinical settings. In our case, prompt management of Graves’ disease contributed to the normalization of calcium levels. This, in turn, supported the differential diagnosis of non-PTH-mediated hypercalcemia.